2022
DOI: 10.3847/1538-3881/ac38ad
|View full text |Cite
|
Sign up to set email alerts
|

Systematic KMTNet Planetary Anomaly Search. II. Six New q < 2 × 10−4 Mass-ratio Planets

Abstract: We apply the automated AnomalyFinder algorithm of Paper I to 2018–2019 light curves from the ≃13 deg2 covered by the six KMTNet prime fields, with cadences Γ ≥ 2 hr−1. We find a total of 11 planets with mass ratios q < 2 × 10−4, including 6 newly discovered planets, 1 planet that was reported in Paper I, and recovery of 4 previously discovered planets. One of the new planets, OGLE-2018-BLG-0977Lb, is in a planetary caustic event, while the other five (OGLE-2018-BLG-0506Lb, OGLE-2018-BLG-0516Lb, OGLE-2019-BL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 68 publications
0
49
3
Order By: Relevance
“…We find that the light curve of OGLE-2016-BLG-1093 is qualitatively similar to that of KMT-2019-BLG-0842Lb (Jung et al 2020) or OGLE-2019-BLG-0960Lb (Yee et al 2021), both of which have much smaller mass ratios (q < 10 −4 ) than our best-fit solution. Following the formalism of Hwang et al (2022)…”
Section: Ground-based Light-curve Analysismentioning
confidence: 99%
“…We find that the light curve of OGLE-2016-BLG-1093 is qualitatively similar to that of KMT-2019-BLG-0842Lb (Jung et al 2020) or OGLE-2019-BLG-0960Lb (Yee et al 2021), both of which have much smaller mass ratios (q < 10 −4 ) than our best-fit solution. Following the formalism of Hwang et al (2022)…”
Section: Ground-based Light-curve Analysismentioning
confidence: 99%
“…In Figure 7, we plot the cumulative distributions of log q for this sample and the 23-planet sample from the MOA-II survey (Suzuki et al 2016). Hwang et al (2022) found a roughly uniform log q distribution over the range −5.0 < log q < −3.7 using the 11 planets from 2018-2019 KMTNet prime fields, and our sample extends the uniform feature to log q ∼ −1.5. Compared with the MOA-II sample, our sample has a higher rate of detections (4/14) below the apparent break in the mass-ratio function of the MOA-II sample, q break = 1.7 × 10 −4 (Suzuki et al 2016).…”
Section: Blended Light and Future High-resolution Observationsmentioning
confidence: 81%
“…The operator identified 9 "planet", 8 "planet/binary", 15 "binary/planet", 83 "binary", and 7 "finite source". Among them, six are known planets (four were previously published, one is in preparation, and KMT-2019-BLG-1552 is analyzed in this paper), seven are planets found by the AnomalyFinder (four were already published by Zang et al (2021); Hwang et al (2022), and three are in preparation). For the remaining events, the operator checked whether the OGLE and/or MOA data points are inconsistent with the KMTNet-based anomalies, cross-checked with C. Han's modeling, and fitted the candidate planetary events to binary-lens single-source (2L1S) model using the online data.…”
Section: Anomalyfinder Results For the 2019-prime Fields And Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microlensing remains the principal method for detecting cool, lowmass exoplanets, including planets beyond the snow-line (Hwang et al 2022;Gaudi 2012); a demographic of particular importance for verifying theories of planetary formation.…”
Section: Introductionmentioning
confidence: 99%